Effect of MobEx Model Intervention Program on Post Lateral Ankle Sprain Functional Outcomes among Athletes (International Journal of Physiotherapy, 2021)
Background: Lateral Ankle Sprain (LAS) is one of the common sports-related soft tissue injuries that occur mainly in weight-bearing positions with plantar flexion and inversion mechanism and affects the athlete's functional ability's at ankle joint. Thus this study was aimed to find out the effects of MobEx intervention on functional ability among athletes.Methods: A total of 27 athletes with unilateral LAS were recruited for this study. The athletes were grouped byrandomization into three groups. The experimental group (n=9) underwent MobEx intervention for six weeks, the placebo group (n=9) underwent placebo intervention for six weeks, and the Control group (n=9) with no interventions. The functional ability was measured by Foot and Ankle Ability Measures (FAAM) questionnaire for daily living, and sports subscale activities were assessed before the intervention, six weeks after intervention, and one month after the intervention.Results: The results revealed a significant difference in athletes' functional ability with a p-value of 0.000 (